Humor Styles as a career management skill: Empowering orientation to change and psychological well-being in higher education students - Αργυροπούλου Κατερίνα (Education Sciences, 2025)
In recent years, the concept of career management skills is increasingly addressed in the approaches of career counseling and career guidance, mainly as a proactive attitude and behavior for career management. Orientation to change and psychological well-being are now considered fundamental factors in addressing the challenges of the 21st century labor market. Humor styles also appear to be a promising preventive resource for facilitating the process of negotiating changes in the current work environment. The present study attempts to investigate the relationship between humor styles, orientation to change, and psychological well-being in a sample of 196 university students. The results show that the use of an appropriate style of humor could positively influence the subjects' mindset and attitude towards existing or future challenges and enhance their subjective sense of well-being. Thus, implementing preventive interventions to increase the usage of adaptive humor styles could help the processes of negotiating changes in career and engaging in continuous personal and career development.